Dosimetric characterization of a mobile accelerator dedicated for intraoperative radiation therapy: Monte Carlo simulations and experimental validation. (December 2022) - Mastella, Edoardo; Szilagyi, Klarisa E.; De Guglielmo, Eleonora; Fabbri, Sara; Calderoni, Francesca; Stefanelli, Antonio; Di Domenico, Giovanni; Turra, Alessandro
Highlights: The angular dependence of a microDiamond detector was evaluated with a home-made phantom. Output factors were measured for both flat-ended and bevelled applicators. Monte Carlo simulations were compared with experimental measurements. Results were in very good agreement with previously published data. Abstract: Purpose: This Technical Note validates previously published data about the dosimetry of the electron beams produced by a mobile accelerator dedicated for intraoperative radiation therapy (IORT). The evaluation of the directional response of a PTW microDiamond detector is presented together with a detailed analysis of the output factors (OFs) for bevelled applicators. Methods: The OFs of the 6, 8, 10 and 12 MeV electron beams produced by a light intraoperative accelerator (LIAC, SIT, Italy) were measured in a commercial water phantom using the microDiamond. A set of flat and bevelled applicators with sizes ranging from 4 to 10 cm was characterized. For bevelled applicators, a correction for the angular dependence of the microDiamond was calculated using a home-made spherical phantom. Correction factors were obtained through measurements performed rotating the accelerator treatment head at 0°, 15°, 30° and 45°. Results: For flat applicators, the average deviation between measured and simulated OFs was (−1.1 ± 0.7)%. The microDiamond showed a higher angular dependence for the 6 MeV beam (∼8% for angles up to 45°, range 92 % ÷ 100 %), while the variations for 8, 10 and 12 MeV beams were ∼ 4 % (range 97 % ÷ 101 %). Correcting for this dependence, the average deviation of the OFs for bevelled applicators was (-0.9 ± 1.6)%. Conclusions: The presented results were in very good agreement with those reported in literature. Very similar deviations were found between flat and bevelled applicators confirming the suitability of our method to determine the angular dependence correction factors of the microDiamond detector.